DAMPAK PANDEMI COVID-19 TERHADAP KINERJA ANGGARAN ASPEK IMPLEMENTASI PADA SATUAN KERJA LINGKUP BPKP RI: ANALISIS PERBANDINGAN - Yudha Perdana Putra (Direktorat Jenderal Anggaran Kementerian, Keuangan Republik Indonesia, 2021)
Multidimensional crisis due to the COVID-19 pandemic has been forcing the Indonesian Government to take a number of extraordinary policies. During the COVID-19 pandemic, the Indonesia's National Government Internal Auditor (BPKP) also affected by these policies. BPKP had to make several adjustments and refocusing on its budget and activities. However, in regular budget performance evaluation at the end of 2020, there are indications that some performance indicators for the implementation of the 2020 budget at units level have decreased. Considering these condition, this study aims to determine whether there are differences in the value of budget performance at units level in BPKP by comparing four variables in measuring budget performance of implementation of the year before and after the COVID-19 pandemic. The Wilcoxon Signed-Rank Test was used to test all variables measuring budget performance on the implementation aspect. The result showed that there were differences in the value of budget performance in BPKP of the year before and after the covid-19 pandemic. Futhermore, two variables which are budget absorption consistency and budget efficiency showing the differences and tendency to decrease. Meanwhile, the other two did not show any difference.